ANALISA PENGARUH KETIDAKSEIMBANGAN SUDUT FASA PADA MOTOR INDUKSI 3 FASA 100HP/75KW SAAT STARTING DAN STEADY STATE MENGGUNAKAN MATLAB SIMULINK - Zadil Hafis; Erhaneli Erhaneli; Anggun Anugrah; Sapannur Bandri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The unbalanced phase angle will affect the stator, torque and speed of the motor. This condition can cause accidents in 3-phase induction motors which make the engine heat up quickly, thereby reducing the actual productivity of the machine. This phase angle deviation will affect the performance of the induction motor which can reduce the strength and ability of the motor. The definition of unbalance is determined based on the NEMA (National Equipment Manufacturer's Association) method. Calculation simulations with Matlab Simulink are carried out for analysis of the impact of balanced phase angles on 3-phase induction motors with an imbalance of 5%, where Phase A = 6⸰, Phase B = 120⸰, and Phase = 240⸰. When the phase angle is not balanced, there is a significant difference in the torque waveform and motor speed, where the wave graph of the torque and motor speed experiences oscillations which results in greater vibration in the motor. Unbalanced phase angle causes an increase in the value of torque and motor speed. At no load the torque is 660 Nm and the speed is 1501Rpm, and at 360 Nm the torque is 1016 Nm. rated motor speed 1497 Rpm,. So that as the load value increases, the torque value will increase and the speed value will decrease. NEMA allows the motor to operate normally under its specifications if the unbalance voltage is not more than 1%. When the unbalanced phase angle is 5% it will cause overheating and losses in the motor increase. To overcome the phase angle imbalance by dereating or lowering the motor rating. When the unbalanced phase angle exceeds 1%, the motor must slow down so that the motor can run properly.